Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.jmarsys.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Southern Benguela upwelling system to fine-scale modifications of the coastal wind

Abstract: International audienceWe analyze the results of a regional model of the Southern Benguela upwelling system forced by wind stress fields derived from QuikSCAT observations. Two different horizontal resolutions are considered for the wind stress: QS25 and QS50, corresponding to native 25 and 50 km grids, respectively. The differences between both products highlight the primary importance of fine-scale momentum fluxes for both the structure and intensity of the wind- and wind-curl-driven upwelling. Using QS25, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…The mesoscale TFB causes wind and surface stress magnitude, divergence, and curl anomalies (Chelton et al, 2004(Chelton et al, , 2007O'Neill et al, 2010O'Neill et al, , 2012Desbiolles et al, 2016). Hogg et al (2009), by using a "crude" parameterization of these surface stress anomalies in an idealized oceanic model, suggest that the mesoscale TFB may weaken the mean circulation by 30% to 40%.…”
Section: Thermal Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesoscale TFB causes wind and surface stress magnitude, divergence, and curl anomalies (Chelton et al, 2004(Chelton et al, , 2007O'Neill et al, 2010O'Neill et al, , 2012Desbiolles et al, 2016). Hogg et al (2009), by using a "crude" parameterization of these surface stress anomalies in an idealized oceanic model, suggest that the mesoscale TFB may weaken the mean circulation by 30% to 40%.…”
Section: Thermal Feedbackmentioning
confidence: 99%
“…Meanwhile, satellite sensors such as scatterometers (e.g., QuikSCAT) have been used to better understand mesoscale air-sea interactions and to demonstrate their global ubiquity and effects on 10-m wind and surface stress (Chelton et al, 2001(Chelton et al, , 2004(Chelton et al, , 2007Chelton & Xie, 2010;Cornillon & Park, 2001;Desbiolles et al, 2017;Gaube et al, 2015;Kelly et al, 2001;Renault, McWilliams, & Masson, 2017;O'Neill et al, 2010O'Neill et al, , 2012. They also motivated model developments and numerical studies that aim to understand the air-sea interaction effects in both the atmosphere and the ocean (Desbiolles et al, 2016;Hogg et al, 2009;Minobe et al, 2008;Oerder et al, 2016Oerder et al, , 2018Renault, Molemaker, Gula, et al, 2016;Seo et al, 2016Seo et al, , 2019Seo, 2017). So far, at the oceanic mesoscale, the scientific community has been focused on two types of air-sea interaction related to the momentum coupling: the Thermal Feedback (TFB) and the Current Feedback (CFB) to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The near-coastal cold bias has been present in various regional model simulations of the EBUS (Penven 2001;Penven 2005;Veitch et al, 2010;Colas et al, 2012). In these studies the authors related the cold bias to the wind being too strong at the shore, which results in an imbalance between Ekman transport and Ekman suction (Capet et al, 2004;Desbiolles et al, 2016). However, such a bias could be also attributed to a warm bias in the satellite-based SST data sets.…”
Section: 1029/2018jc014051mentioning
confidence: 99%
“…As a consequence, the enhanced equatorward pressure gradient forces a shoreward geostrophic current in displacing offshore the surface Ekman current at the coast (see Figure A6d). Indeed Desbiolles et al (2016) showed that an overestimated coastal wind would impact negatively the structure of the meridional and zonal surface currents and the upwelling dynamics in the EBUS of the Benguela region. They showed that the cross-shore structure of the alongshore winds impact both the offshore and northward surface flows increasing the Ekman transport and the geostrophic adjustment and reducing the intensity and shallowness of the poleward undercurrent.…”
Section: 1029/2018jc014051mentioning
confidence: 99%
“…Surface wind vectors are indeed the key drivers of oceanic and atmospheric processes that regulate the global and regional climate [e.g., Ricciardulli and Wentz, 2013]. Ocean winds are routinely used as the primary forcing function of numerical hydrodynamic models of the ocean circulation [e.g., Grima et al, 1999; Carton and Giese, 2009;Wunsch et al 2009;Desbiolles et al, 2016] and of surface gravity waves [e.g., et al, 1988;Tolman 2002] at global and regional scales. Ocean winds are considered as the most important variable for investigating storm surges and wave forecasts at various space and time scales [Debernard et al, 2002].…”
mentioning
confidence: 99%